A szimbolikus terek változása Kolozsváron : 1945-1967 - Lakatos, Artur (Közép-Európai Közlemények, 2015)
This paper is dealing with the issue of metamorphosis of symbolic spaces in the Transylvanian city of Cluj (Kolozsvár) during the decades of the Romanian Socialist regime, including its social, cultural and political aspects. The research synthesized and concluded modifications intervened in denominations of streets and squares, giving a special attention to the symbolic secondary meaning of the change in cause. The final result is a documented synthesis of the way how the symbolic space of the city in cause was modified, through a gradual suppression of Hungarian symbols and the promotion of Internationalist Communist, and later Romanian national symbols. The focus is especially on the city center, but where it is relevant, the Communist-style built neighborhoods, with all of their specific characteristics, are also presented. The presentation is focused on three main directions: planning of city landscape accordingly to the standards of the ruling ideology, the faith of the main statues and other historical monuments during the Communist era, and the changes intervened in street denominations.